Learn and Play Activities to Support Early Childhood Teacher’s Understanding of Electrical Energy Concepts - Ihtiari Prastyaningrum; Alisa Alfina; Swasti Maharani (Sakura Digital Nusantara, 2026)
Purpose – This study aims to explore and strengthen early childhood education (ECE) teachers’ understanding of fundamental electrical energy concepts, including sources of electrical energy, energy conversion, and simple electrical circuits. It also seeks to equip teachers with the ability to design Learn and Play–based science activities that are concrete, exploratory, and grounded in children’s daily experiences. Methods – The research employed a mixed-methods approach, combining quantitative testing and qualitative phenomenological analysis. The study involved 20 ECE teachers from six institutions in Madiun City and Madiun Regency. The intervention was carried out across three phases: basic training, mentoring on theoretical and practical concepts, and pedagogical assistance. Data were obtained through pre-tests, post-tests, observation, learning plan assessments, and in-depth interviews. Findings – Results revealed significant improvements in teachers’ conceptual understanding and pedagogical readiness. Teachers demonstrated enhanced literacy regarding electrical energy, increased confidence in explaining basic scientific concepts, and improved skills in designing interactive Learn and Play activities. The mentoring phases also showed that teachers could connect personal experiences with scientific explanations, leading to more meaningful learning preparations and effective classroom implementation. Research implications – Strengthening teachers’ scientific literacy through structured mentoring can reduce misconceptions in early childhood science learning. The model used in this study may serve as a reference for ECE professional development programs focusing on science education. Originality – This study offers a unique integration of Learn and Play activities with phenomenological exploration of teachers’ personal experiences related to electrical phenomena. It fills the research gap on electrical concept literacy among early childhood teachers, a topic rarely examined in previous studies.